Exploring the Relationship between Budget Transparency and Employee Engagement within the Department of Agrarian Reform (DAR) Masbate - Cos, Jelisa Gabriela (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between budget transparency and employee engagement among employees of the Department of Agrarian Reform (DAR) Masbate. It was anchored on Agency Theory, Social Exchange Theory, and Organizational Transparency Theory, which explain how openness, fairness, and accessible information may influence employee trust, motivation, and participation. The study employed a quantitative descriptive-correlational research design using a researcher-made structured questionnaire administered to thirty (30) current employees of DAR Masbate selected through purposive sampling. Data were analyzed using frequency, percentage, weighted mean, ranking, and Pearson Product-Moment Correlation Coefficient at the 0.05 level of significance. Findings showed that budget transparency was generally rated high to very high, particularly in access to budget information, communication of budget priorities, and accountability in budget management, while employee participation in budget-related activities received a relatively lower rating. Employee engagement was rated very high in terms of dedication, absorption, and vigor. Among the dimensions of budget transparency, accountability in budget management had the greatest influence on employee engagement. The study found a moderate positive and statistically significant relationship between budget transparency and employee engagement, with an r-value of 0.54. The study concludes that stronger budget transparency is associated with higher employee motivation, commitment, and involvement. It recommends improving timely budget communication, employee participation, accountability systems, professional development, recognition, and regular monitoring. The study supports SDG 16, SDG 8, and SDG 11 by promoting transparent institutions, productive work engagement, and improved public service delivery. Its sustainability impact lies in strengthening institutional governance, employee performance, and community-oriented agrarian reform services.